2018
DOI: 10.1177/0146621618798669
|View full text |Cite
|
Sign up to set email alerts
|

A Sandwich Standard Error Estimator for Exploratory Factor Analysis With Nonnormal Data and Imperfect Models

Abstract: This article is concerned with standard errors (SEs) and confidence intervals (CIs) for exploratory factor analysis (EFA) in different situations. The authors adapt a sandwich SE estimator for EFA parameters to accommodate nonnormal data and imperfect models, factor extraction with maximum likelihood and ordinary least squares, and factor rotation with CF-varimax, CF-quartimax, geomin, or target rotation. They illustrate the sandwich SEs and CIs using nonnormal continuous data and ordinal data. They also compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…An EFA was conducted after the validation and reliability analyses (Zhang et al, 2019). Following guidelines given Watkins (2018), first, a testing for normality of distribution using Kolmogorv-Smirnov parameter was carried out.…”
Section: Phase 4: Exploratory Factor Analysismentioning
confidence: 99%
“…An EFA was conducted after the validation and reliability analyses (Zhang et al, 2019). Following guidelines given Watkins (2018), first, a testing for normality of distribution using Kolmogorv-Smirnov parameter was carried out.…”
Section: Phase 4: Exploratory Factor Analysismentioning
confidence: 99%
“…As comparisons, we also conduct CFA and EFA with regular target rotation. Extended target rotation and target rotation are conducted using the R package EFAutilities (Zhang, Jiang, Hattori, & Trichtinger, 2018); the CFA is conducted using the R package lavaan (Rosseel et al, 2017). We include the R code of conducting EFA with extended target rotation in Appendix B 1…”
Section: Empirical Illustrationsmentioning
confidence: 99%
“…Extended target rotation incorporates researchers’ substantive knowledge more effectively than other rotation methods. Extended target rotation has been implemented in an R package EFAutilities (Zhang et al, 2018). We demonstrated extended target rotation with an MTMM study and a study of eight cognitive tests.…”
Section: Concluding Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later authors (Browne, 2001; Gebhardt, 1968; Hattori et al, 2017; Jennrich, 2004, 2006; Kiers, 1994; Rozeboom, 1992) showed that other rotation criteria were also prone to this phenomenon. Given these findings, it is surprising that few modern EFA programs allow users to initiate factor rotations from different starting values (important exceptions are Bernaards & Jennrich, 2005; Browne et al, 2008; Muthén & Muthén, 2017; Waller, 2020; Zhang et al, 2020). Perhaps this missing option explains, in part, why many applied researchers are seemingly unaware of the prevalence and correlates of LS in EFA.…”
mentioning
confidence: 99%